Vulnerability analysis of industrial RC precast buildings designed according to modern seismic codes. (1st March 2018) - Ercolino, Marianna; Bellotti, Davide; Magliulo, Gennaro; Nascimbene, Roberto
Highlights: The design is mostly influenced by the seismic details required by the code. In many cases the seismic action does not give the largest demand on the structures. The capacity of the structures is lightly influenced by the seismicity of the site. Multi-stripe analyses show a large overstrength of the structures. A comparison between different modelling approaches is performed. Abstract: Seismic performance-based design approach is currently implemented in modern building codes. Design requirements and provisions ensure an adequate structural performance under different intensity levels of seismic action. However, the probability of attainment of a performance level is implicitly considered in the code design approach (provisions and requirements); for instance, the minimum requirements in concrete structures cannot be simply correlated to the probability of collapse of the building as well as to its overall structural response. The aim of this work is to assess the vulnerability with respect to the collapse limit state of industrial single-story RC precast buildings designed according to the current Italian seismic code. The comparison between the Italian code and the Eurocodes is provided throughout the paper. A parametric study is performed by investigating the safety against the collapse of 40 RC single-story precast structures. Multi-stripe analyses are performed by non-linear dynamic analyses at 10 intensity levels. The fragility of the structures is defined by means of the incremental N2 method, which has been demonstrated to be a suitable method for evaluating the collapse capacity of single-story precast buildings. The results demonstrate that the buildings are safe against the collapse mainly because of the structural overstrength with respect to seismic actions. The modelling assumptions are also validated in order to demonstrate the negligible influence of the cracking on the collapse as well as the importance of the geometrical nonlinearities for precast buildings.